Therapeutic Effects and Molecular Mechanism of Banxia Xiexin Decoction on Intestinal Mucosal Barrier Function in Sepsis - Dai, Wen; Zhou, Lei; Hao, Hao; Wang, Diankui; Zhang, Feihu; Wang, Peng; Wang, Lin; Kong, Li (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: mitochondrial autophagy